THE EPIDEMIOLOGICAL AND IMMUNOLOGICAL EFFECTIVENESS OF VACCINATION OF HEPATITIS A IN ORGANIZED GROUPS OF MILITARY PERSONNEL. IMMUNOLOGICALLY EFFECTIVE DOMESTIC VACCINE «HEP-IN-A-VAC» - V. G. Akimkin; S. I. Korotchenko; A. V. Alimov; V. A. Shevtsov (Сеченовский вестник, 2012)
Since 2004 the incidence of hepatitis A of conscripts declined by more than 70 times, which happened primarily due to vaccination. The paper under review presents the characteristics of a phased strategy of specific prevention of hepatitis A, provides the comparative analysis of the immunological and epidemiological effectiveness of domestic (HEP-A-in-VAC) and foreign vaccines. Showing low reactogenicity and immunogenicity of an improved high enough vaccine HEP-A-in-VAC.